A17 ASSOCIATION BETWEEN HOST INFLAMMATION-RELATED PROTEOMICS AND GUT MICROBIOME IN HEALTHY FIRST-DEGREE RELATIVES OF CROHN'S DISEASE PATIENTS. (26th February 2020) - Raygoza Garay, J; Turpin, W; Smith, M; Goethel, A; Guttman, D S; Croitoru, K
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory condition of the gastrointestinal tract. It has been suggested that the cause of CD is due to microbial and environmental factors that induce an imbalance of the immune system in genetically susceptible individuals. The Genetic Environmental Microbial (GEM) Project is a prospective study of asymptomatic first-degree relatives (FDR) of CD patients, recruited to understand the biological and environmental determinants of disease development. Aims: Here, we aim to define the relationships between the host inflammation-related proteomics and gut microbiome composition in a cohort of 320 healthy CD FDRs at the time of recruitment. Methods: We measured 92 inflammation-related serum proteins using the Olink® 'Inflammation' proteomics panel. Stool microbial composition was determined by sequencing the V4 region of the 16S rRNA. To assess the relationship between serum protein levels and the relative abundance of microbial taxa, we used a zero-inflated two-part regression model corrected for multiple-comparisons (significant association at p< 2.75 × 10 –4 ). Results: We found fifteen serum proteins that were each significantly associated with the relative abundances of one to five genera or families, depending on the analyte. Of particular interest to CD, the relative abundance of both TNF-β and LIGHT (TNFSF14) were negatively associated with the relative abundance of bacteria in the Parabacteroides genus. Both TNF-β and LIGHT are members of the Tumor Necrosis Factor (TNF) family of cytokines with roles in mucosal healing, IgA production, and in control of innate lymphoid cells (ILCs). These processes have been hypothesized to have critical roles in CD pathology. Interestingly, prior work also demonstrates that Parabacteroides distasonis enhanced colitis in a mouse model and was isolated from a gut wall-cavitating microlesion in a patient with severe CD. Other inflammation-related proteins with significant taxa associations include IL-2, IL-33, OSM, 4E_BP1, IL-1α, ARTN, AXIN1, and CDCP1. Conclusions: This study highlights the associations between inflammation associated proteomics and gut microbial taxa in asymptomatic FDRs of CD patients. The mechanisms explaining this association will require further analysis. Funding Agencies: CCC The Leona M. and Harry B. Helmsley Charitable Trust